The Nucleotide Sequence of the Matrix (M) Protein Gene of Newcastle Disease Virus (NDV) Strain AF 2240 - Jemain, Siti Fathimah Putery (1999)
The complete nucleotide sequence of the matrix (M) protein gene of the local Newcastle disease virus (NDV) strain AF 2240 was determined. Based on consensus primers, several segments of the M gene were reverse transcribed and amplified by the polymerase chain reaction. The RT-PCR products were cloned into a plasmid vector pCR™2.1. The DNA inserts in the clones were then cycle-sequenced. The start and polyadenylation signals have been identified. Assuming that the M gene starts and terminates at these sequences, the M gene is 1223 nucleotides long and encodes an open reading frame of 364 amino acids, corresponding to a polypeptide calculated molecular weight of 40 kDa. The M protein, is both hydrophobic and basic. Phylogenetic analysis shows that the strain has a close relationship with the North American Fontana strain. The M protein amino acid sequence also shows similarities with members of the Rub ulavirus genus such as the Simian virus 5, the human parainfluenza virus type 4 and the mumps virus. Similarities of the amino acid sequence also exist between the local strain and other members of the Paramyxovirus and Morbillivirus genus.